New missense variants in RELT causing hypomineralised amelogenesis imperfecta. Issue 5 (21st February 2020) - Nikolopoulos, Georgios; Smith, Claire E.L.; Brookes, Steven J.; El‐Asrag, Mohammed E.; Brown, Catriona J.; Patel, Anesha; Murillo, Gina; O'Connell, Mary J.; Inglehearn, Chris F.; Mighell, Alan J.
Abstract: Amelogenesis imperfecta (AI) is a heterogeneous group of genetic diseases characterised by dental enamel malformation. Pathogenic variants in at least 33 genes cause syndromic or non‐syndromic AI. Recently variants in RELT, encoding an orphan receptor in the tumour necrosis factor (TNF) superfamily, were found to cause recessive AI, as part of a syndrome encompassing small stature and severe childhood infections. Here we describe four additional families with autosomal recessive hypomineralised AI due to previously unreported homozygous mutations in RELT . Three families carried a homozygous missense variant in the fourth exon (c.164C>T, p.(T55I)) and a fourth family carried a homozygous missense variant in the 11th exon (c.1264C>T, p.(R422W)). We found no evidence of additional syndromic symptoms in affected individuals. Analyses of tooth microstructure with computerised tomography and scanning electron microscopy suggest a role for RELT in ameloblasts' coordination and interaction with the enamel matrix. Microsatellite genotyping in families segregating the T55I variant reveals a shared founder haplotype. These findings extend the RELT pathogenic variant spectrum, reveal a founder mutation in the UK Pakistani population and provide detailed analysis of human teeth affected by this hypomineralised phenotype, but do not support a possible syndromic presentation in all those with RELT ‐variant associated AI. Abstract :